2013
DOI: 10.3934/dcds.2013.33.2241
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics for symmetric planar maps

Abstract: We consider sufficient conditions to determine the global dynamics for equivariant maps of the plane with a unique fixed point which is also hyperbolic. When the map is equivariant under the action of a compact Lie group, it is possible to describe the local dynamics. In particular, if the group contains a reflection, there is a line invariant by the map. This allows us to use results based on the theory of free homeomorphisms to describe the global dynamical behaviour. We briefly discuss the case when reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…If f is invertible then we define α 2 (p) in a similar way. Lemma 2.8 (Lemma 3.1 in [3]). Let f : R n → R n be a homeomorphism such that f (0) = 0.…”
Section: Background and Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…If f is invertible then we define α 2 (p) in a similar way. Lemma 2.8 (Lemma 3.1 in [3]). Let f : R n → R n be a homeomorphism such that f (0) = 0.…”
Section: Background and Definitionsmentioning
confidence: 99%
“…In Alarcón et al [3], we provide a list of symmetry groups for which the corresponding equivariant maps may possess a local saddle. There it is shown that the only symmetry groups that admit a local saddle are Z 2 ( −Id ),…”
Section: Symmetric Global Saddlementioning
confidence: 99%
See 3 more Smart Citations